An Investigation of the Chemical Composition of Precipitation in and around Kuala Lumpur - Lee, C. K.; Low, K. S. (1984)
Individual rain event samples were collected at three sites in and around Kuala Lumpur from May, 1.982 to May 1983. The samples were analysed for pH, anions (sulphate, nitrate, chloride and fluoride) and cations (calcium, magnesium, sodium and potassium). Correlation and regression analyses indicated that the major anions appeared to be more closely associated with the cattons than the hydrogen ion. Pollutants from both natural and anthropogenic sources appeared to have contributed to the chemical composition of precipitation.